Book - Brookfield, Karen (New York : A.A. Knopf : Distributed by Random House, 1993)
Text and photographs trace the evolution of the written word, how the alphabet grew out of pictures, the development of papermaking, bookbinding, children's books, and more.
What is writing? -- First signs -- Writing with signs -- Egyptian writing -- ABC... -- Before paper -- Paper -- Medieval psalter -- Manuscript books -- Books from Asia -- Islamic books -- Getting ready to print -- Typesetting -- On press -- Early printed books -- Typefaces -- Binding -- Illustrated books -- Learning words -- Handwriting -- Children's books -- Words at work -- Typewriter -- Book market -- Keeping your words.
Includes index.
Keywords: Books -- History -- Juvenile literature; Books -- History